مساهمة التسويق الرقمي في تحسين جودة الخدمات الصحية في الجزائر -من وجهة نظر المريض – - اعبيد, عواطف; شرون, رقية (جامعة الوادي - University of Eloued, 2023)
هدفت الدراسة الى توضيح دور ومساهمة التسويق الرقمي في تحسين جودة الخدمة الصحية من وجهة نظر المريض، ولتحقيق أهداف الدراسة تم تصميم استبانة ضمت مجموعة من العبارات معبرة عن ابعاد متغيري الدراسة، المتمثلة في التسويق الرقمي، وجودة الخدمة الصحية. حيث تم توزيع 100 استبانة على عينة عشوائية من المرضى ، وتم استرجاع (74) قابلة للتحليل. وخلصت الدراسة الى جملة من النتائج أهمها: ان استخدام التسويق الرقمي يساهم في تحسين جودة الخدمة الصحية بالعيادات الخاصة في الجزائر ، خاصة من خلال التسويق عبر البريد الالكتروني، والتسويق عبر الموقع الالكتروني The paper aimed to study the contribution of digital marketing in improving the quality of health services from the patient's point of view. For achieving the objectives of the study, a questionnaire has been designed (including a set of statements expressing the dimensions of the study's variables, which are digital marketing and health service quality) and distributed to a random sample of patients (100 questionnaires), where 74 questionnaires were retrieved and accepted for analysis. The study has concluded that The use of digital marketing has an impact on improving the quality of health service in private clinics in Algeria, especially marketing via e-mail, andmarketing via the website.
The contribution of digital marketing in improving the quality of health services in Algeria from the patient's point of view -
مقال
Keywords: التسويق الرقمي ; الخدمات الصحية ; جودة الخدمة الصحية; digital marketing, health services, health service quality